KUALITAS BOLU KUKUS DENGAN SUBSTITUSI TEPUNG TEMPE KACANG GUDE (Cajanus cajan) dan TEPUNG UBI JALAR UNGU (Ipomoea batatas) SEBAGAI PEMANIS: bolu kukus, tepung ubi jalar ungu, tepung tempe kacang gude, pemanis alami - Sugianto, Emanuella Priscilia; Swasti, Yuliana Reni; Pranata, Franciscus Sinung (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
Steamed sponge cake is a traditional snack that is often found in markets with a variety of attractive colors. Steamed sponge cake is made from wheat flour, granulated sugar, liquid milk, and eggs. This research used other additional flour, namely pigeon pea tempeh flour and purple sweet potato flour. The research carried out aimed to determine the effect of the substitution of pigeon pea tempeh flour and purple sweet potato flour as natural sweeteners on the quality of steamed sponge cake based on chemical, physical, microbiological, and organoleptic parameters. The experimental design in this study used a Completely Randomized Design (CRD) with variations of wheat flour, pigeon pea tempeh flour, and purple sweet potato flour, respectively, namely control 80:0:0, treatment (A) 40:24:16, treatment (B) 40:20:20, and treatment (C) 40:16:24. The steamed sponge cake in this study contained water content of 35.25-37.76%, ash content of 1.23-2.10%, the fat content of 5.62-9.76%, the protein content of 8.28-10.04%, the carbohydrate content of 43.13-49.73%, insoluble fiber content of 3.59-26.35%, soluble fiber content of 1.67-20.54%, total sugar content of 6.57-24.83%, volume expansion of 55,49-77,45%, texture hardness of 3.18-8.49 N, and microbiology test of Total Plate Number and Yeast Mold Number in accordance with sweet bread standards according to SNI 01-3840-1995. Steamed sponge cake with the substitution of pigeon pea tempeh flour and purple sweet potato flour, which produced the best treatment based on physical, chemical, microbiological, and organoleptic quality, was treatment B (40:20:20).